Surgical trial in traumatic intracerebral hemorrhage (STITCH(Trauma)): study protocol for a randomized controlled trial - Gregson, Barbara A.; Unterberg, Andreas; McNamee, Paul (Trials, 2012)
Intracranial hemorrhage occurs in over 60% of severe head injuries in one of three types: extradural (EDH); subdural (SDH); and intraparenchymal (TICH). Prompt surgical removal of significant SDH and EDH is established and widely accepted. However, TICH is more common and is found in more than 40% of severe head injuries. It is associated with a worse outcome but the role for surgical removal remains undefined. Surgical practice in the treatment of TICHs differs widely around the world. The aim of early surgery in TICH removal is to prevent secondary brain injury. There have been trials of surgery for spontaneous ICH (including the STICH II trial), but none so far of surgery for TICH.